Faculty manual - Lal Bahadur Shastri National Academy of Administration (Mussoorie, 1995)
This is a faculty manual of Lal Bahadur Shastri National Academy of Administration(LBSNAA), Mussoorie.
Keywords: Training - Manuals, handbook